2021
DOI: 10.4103/njcp.njcp_676_20
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polymerization mode and layer thickness on monomer released from bulk fill composite resins

Abstract: Background: Residual monomers released from composite resins have cytotoxic, mutagenic, and estrogenic effects. Mode of polymerization and application thickness are important for monomer release. Aims: The aim of this study was to investigate the effects of different modes of a third-generation light-curing unit (LCU) and layer thickness on residual monomer released from two different bulk-fill composite resins. A total of 80 samples were prepared for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To prevent the cytotoxic effects that can arise from unpolymerized monomers, irradiation time needs to be expanded in the case of thicker increments. In this regard, it was shown that from photopolymerized 2 mm-thick resin composite increments, fewer monomers, such as TEGDMA, Bis-GMA, and UDMA, were released compared to thicker layers that were identically cured [54].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the cytotoxic effects that can arise from unpolymerized monomers, irradiation time needs to be expanded in the case of thicker increments. In this regard, it was shown that from photopolymerized 2 mm-thick resin composite increments, fewer monomers, such as TEGDMA, Bis-GMA, and UDMA, were released compared to thicker layers that were identically cured [54].…”
Section: Discussionmentioning
confidence: 99%
“…When composite resins are not sufficiently polymerized, their physical and mechanical properties weaken and residual monomer is released into the environment. These residual monomers can cause estrogenic, genotoxic and cytotoxic effects (7). Possible toxicological reactions are evaluated in vitro using cell cultures in cytotoxicity tests.…”
Section: Degree Of Conversion Micro Hardness and Cytotoxicity Of Bulk...mentioning
confidence: 99%